Formulation and Validation of Herbosomes Loaded Herbal Topical Preparation for Eczema - Vidhale, Gunjan S.; Waghulkar, V.M.; Jadhao, Dr. M.P.; Game, Dr. M.D.; Jawarkar, S.G. (Asian Journal of Pharmaceutical Research and Development, 2024)
Eczema, a common inflammatory skin condition, presents significant challenges in management due to its multifactorial etiology and diverse clinical manifestations. Characterized by pruritus, erythema, and eczematous lesions, eczema negatively impacts patients’ quality of life and requires comprehensive treatment approaches. Conventional treatments include topical corticosteroids, moisturizers, and immunomodulators, which provide symptomatic relief but may be associated with adverse effects and limited long- term efficacy. In recent years, there has been growing interest in alternative therapies, including herbal medicines, probiotics, and phototherapy, for eczema management.Herbal remedies, such as Berberis Aquifolium, have shown promise in eczema treatment due to their anti-inflammatory and antimicrobial properties. Novel drug delivery systems, such as Herbosomes, offer innovative approaches to enhance the bioavailability and efficacy of herbal constituents for eczema management. In the present study, the Berberis Aquifolium herbosomal lotion was formulated and used for an analytical method that is Ultraviolet spectroscopy (UV) which is developed and validated. In the method development solvent used is distilled water. The method is validated for linearity, range, limit of detection, limit of quantification, precision, and robustness. The developed analytical method was found to be simple, reliable, precise, and robust. The validated UV Spectroscopy method was successfully applied for quantification of Berberis Aquifolium loaded Herbosomal lotion.